2013
DOI: 10.1155/2013/493656
|View full text |Cite
|
Sign up to set email alerts
|

Passive Repetitive Stretching for a Short Duration within a Week Increases Myogenic Regulatory Factors and Myosin Heavy Chain mRNA in Rats′ Skeletal Muscles

Abstract: Stretching is a stimulation of muscle growth. Stretching for hours or days has an effect on muscle hypertrophy. However, differences of continuous stretching and repetitive stretching to affect muscle growth are not well known. To clarify the difference of continuous and repetitive stretching within a short duration, we investigated the gene expression of muscle-related genes on stretched skeletal muscles. We used 8-week-old male Wistar rats (N = 28) for this study. Animals medial gastrocnemius muscle was str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The expression of MyoD in the soleus had increased for 24 hours after stretching for 15 minutes [18]. Either continuous or repetitive short-duration stretching of muscles for 1 week increased the mRNA expression levels of MyoD, myogenin, and embryonic MyHC relative to those of unstretched muscles [6]. In clinical rehabilitation, the duration of treatment tends to be short.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of MyoD in the soleus had increased for 24 hours after stretching for 15 minutes [18]. Either continuous or repetitive short-duration stretching of muscles for 1 week increased the mRNA expression levels of MyoD, myogenin, and embryonic MyHC relative to those of unstretched muscles [6]. In clinical rehabilitation, the duration of treatment tends to be short.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical environment and changes in muscle structure and physiology suggest that there may be pathways within muscle cells through which mechanical signals can be converted into chemical signals that in turn generate numerous, specific downstream events that determine the muscle's form and function [5]. Several studies have reported that muscle stretching induces muscle growth and hypertrophy [68]. Such mechanical stimulation is thought to be helpful for patients with muscle weakness and also applicable to clinically unconscious patients and those with paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that MRF gene expression levels are increased by short‐term passive repetitive stretching (Kamikawa et al . ). However, other researchers have reported that MRFs regulate muscle mass but not fiber‐type conversion during long‐term resistance training (Aguiar et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, recent studies have shown that MyoD controls myogenesis, while Myf5 and myogenin mRNA expression do not, during the terminal differentiation phase of bovine myoblasts (Muroya et al 2005). Our review of previous studies of MRFs revealed that they have focused primarily on gene expression (Ropka-Molik et al 2011), cloning (Zhang et al 2014) and functional experiments (Kablar et al 2003) in rats and humans, while few have explored the mRNA expression patterns of muscle-specific genes during external stimulation (Aguiar et al 2013;Kamikawa et al 2013) in the postnatal development of ruminant animals. The transcript profiles of MyoD and Myf5 have been shown to be related to myosin heavy chain isoform types in bovine adult muscles (Muroya et al 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation